Nucleus Accumbens Core and Shell are Necessary for Reinforcer Devaluation Effects on Pavlovian Conditioned Responding - Singh, Teghpal; McDannald, Michael; Haney, Richard; Cerri, Domenic; Schoenbaum, Geoffrey (Frontiers in Integrative Neuroscience, 2010)
The nucleus accumbens (NA) has been hypothesized to be part of a circuit in which cue-evoked information about expected outcomes is mobilized to guide behavior. Here we tested this hypothesis using a Pavlovian reinforcer devaluation task, previously applied to assess outcome-guided behavior after damage to regions such as the orbitofrontal cortex and amygdala that send projections to NA. Rats with sham lesions or neurotoxic lesions of either the core or shell subdivision of NA were trained to associate a 10 sec CS+ with delivery of three food pellets. After training, half of the rats in each lesion group received food paired with illness induced by LiCl injections; the remaining rats received food and illness unpaired. Subsequently, responding to the CS+ was assessed in an extinction probe test. Both sham and lesioned rats conditioned to the CS+ and formed a conditioned taste aversion. However only sham rats reduced their conditioned responding as a result of reinforcer devaluation; devalued rats with lesions of either core or shell showed levels of responding that were similar to lesioned, non-devalued rats. This impairment was not due to the loss of motivational salience conferred to the CS+ in lesioned rats as both groups responded similarly for the cue in conditioned reinforcement testing. These data suggest that NA core and shell are part of a circuit necessary for the use of cue-evoked information about expected outcomes to guide behavior.